AN OVERVIEW ON NATURAL WOUND HEALING PROCESS WITH SOME INDIGENOUS PLANTS AS WOUND HEALER (Journal of Pharmaceutical Negative Results, 2022)
Skin provides a protective barrier against any damage. Wound healing involves various cellular mechanisms. Wound is defined as the injury which may be due to physical, chemical or thermal means represents a major global health challenge as it can put financial and social stress especially on patients and their families. Wound healing process is a complex process having a series of different steps. So, a good wound healing management is required for the whole community. Historical records show the important role of medicinal in treatment of various ailments. In early 1900’s the herbalism declined in Europe and the United States due to expansion of Allopathic medicine but now a days the trend again moves to Herbalism due to uneasiness caused by side effects of synthetic drugs. Herbal drugs in comparison to synthetic drugs cause minimal side effects and least resistance issues. In this review article information regarding natural wound healing process and plants possessing wound healing properties are gathered.